Synoviocyte-Derived Extracellular Matrix and bFGF Speed Human Chondrocyte Proliferation While Maintaining Differentiation Potential - Truong, Rachel D.; Bernier, Megan A.; Dennis, James E.; Kean, Thomas J. (Frontiers in Bioengineering and Biotechnology, 2022)
Improving the ability of human chondrocytes to proliferate, while maintaining their differentiation potential, has presented a great challenge in cartilage tissue engineering. In this study, human chondrocytes were cultured under four unique growth conditions at physiologic oxygen tension: tissue culture plastic (TCP) only, synoviocyte matrix (SCM)–coated flasks only, SCM-coated flasks with bFGF media supplement, and TCP with bFGF media supplement. The results indicated that, compared to standard TCP, all test conditions showed significantly increased cell expansion rates and an increase in both glycosaminoglycan (GAG) and collagen content during redifferentiation culture. Specifically, the combined SCM + bFGF growth condition showed an additive effect, with an increase of approximately 36% more cells per passage (5–7 days) when compared to the SCM alone. In conclusion, the results of this study demonstrate that bFGF and SCM can be used as supplements to enhance the growth of human chondrocytes both as individual enhancers and as a combined additive.